Sporting Legacy: From Cricket To Football - Abduraximova Nozima; Ernazarova Zulayho; Dilnoza Shamuratova Jamolovna (Genius Journals, 2024)
This article delves into the rich sporting heritage of the United Kingdom, focusing on traditional sports like cricket and rugby, as well as the modern phenomenon of football. It examines the profound impact these sports have had on national identity and social cohesion, creating a sense of unity and pride among the British populace. Through an extensive literature review and a qualitative research methodology, this study discusses the historical context, cultural significance, and the broader societal implications of sports in the UK. Additionally, the paper explores how these sports have evolved in response to changing societal dynamics and global influences. By analyzing both historical and contemporary perspectives, the article provides a comprehensive understanding of the role sports play in shaping British society
Keywords: United Kingdom; Cricket; Rugby; Football